The influence of sales promotion on store choice - Cunha, S. M. da.; Crespo de Carvalho, J. (34th EMAC Conference, 2005)
This study evidences the influence that the sales promotions have on store choice. Sales promotion may lead to a change of store. The consumers buy their purchases in one store instead of another since the sales promotions vary from one store to another. This paper presents a conceptual model of the process of assessing a retail format that includes the sales promotion. The objective is to examine: if sales promotions are a store choice criteria, and what types of store choice criteria have greater influence on the store patronage intentions. To test the conceptual model is used a sample of hypermarket customers.